Isotopic examination of links between diet, social differentiation, and DISH at the post‐medieval Carmelite Friary of Aalst, Belgium. Issue 2 (14th November 2013) - Quintelier, Kim; Ervynck, Anton; Müldner, Gundula; Van, Wim; Richards, Michael P.; Fuller, Benjamin T.
ABSTRACT Stable isotope ratios (δ13C and δ15N) were measured in human burials from the post‐medieval (16th–18th c. AD) Carmelite friary burial grounds at Aalst, a town in Flanders, Belgium. Dietary patterns of 39 adult individuals were analyzed, from a mixed monastic and lay population buried in three different locations, reflecting groups with differing social status. The data show significant variation in the consumption of perhaps meat, but certainly also marine protein between females and males. This result represents a remarkable continuity with medieval dietary patterns, suggesting that the social and economic changes of the early modern period had a limited effect on everyday life. When both sexes were examined together, individuals buried in the cloister garth consumed significantly less marine protein compared to people buried in the church, likely reflecting social stratification. No statistical differences were observed between isotopic values from the church and the cloister alley, suggesting a similarly diverse diet of the monastic part of the buried population and that of the richer lay population. Finally, the hypothesis that diffuse idiopathic skeletal hyperostosis (DISH) is linked to a diet rich in animal protein was tested. No systematic or statistically significant differences between pathological and non‐pathological bones from the same individuals affected with DISH were observed, and no statistical differences were found between individuals with DISH and individuals without DISH. Am J Phys Anthropol 153:203–213, 2014. © 2013 Wiley Periodicals, Inc.